35 years from the fall of the Berlin Wall: consequences and modern tendencies - Gajić, Aleksandar (Napredak, 2025)
The paper examines modern processes in Europe three and a half decades after the fall of the Berlin Wall. The time distance offers more favourable conditions for perceiving the Berlin wall and its role, as well as the causes of the fall of real socialism and the ensuing processes by using the historical and comparative method, and also the synthetic-analytical method. The paper is divided into three segments: the first one deals with the demystification of the Berlin Wall and its historical role from the time of its construction to its destruction; the second segment deals with the analysis of direct and long-term consequences of the fall of the Berlin Wall, while the third one is dedicated to the forms of changes and their tendencies in Europe. The conclusion of the paper synthetizes the findings from all three chapters and gives a critical review of today’s state of affairs on the European continent.
Keywords: Berlin Wall; unification of Germany; fall of socialism; transition; geopolitics